Comparison of Techniques and Solvents on the Antimicrobial and Antioxidant Potential of Extracts from Acacia dealbata and Olea europaea - Anabela Borges (2020)
Ethnopharmacological use of plant natural extracts has been known since ancient times. The optimization of plant molecule extraction is fundamental in obtaining relevant extraction yields. The main purpose of this study was to understand the role of different extraction techniques (solid-liquid, ultrasound, Soxhlet, and microwave) and solvents (water, methanol, ethanol, acetone, dichloromethane, and hexane) on the antimicrobial and antioxidant activities of extracts from Olea europaea (olive) and Acacia dealbata (mimosa). Crude plant extracts were evaluated for their antimicrobial activity against Staphylococcus aureus and Escherichia coli by the disk diffusion method. The antioxidant capacity of the extracts was determined by ABTS (2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid)) and DPPH (2,2-diphenyl-1-picrylhydrazyl) methods. In terms of extraction yield, ultrasound extraction and the solvents methanol, acetone (O. europaea) or water (A. dealbata) were found to be the best options. However, ethanol and acetone proved to be the best solvents to extract compounds with antimicrobial activity and antioxidant capacity, respectively (regardless of the extraction method employed). Soxhlet and microwave were the best techniques to extract compounds with antimicrobial activity, whereas any of the tested techniques showed the ability to extract compounds with antioxidant capacity. In most of the cases, both plant extracts (mimosa and olive) were more efficient against S. aureus than E. coli. In the present study, both mimosa and olive leaf crude extracts proved to have antimicrobial and antioxidant activities, increasing the demand of these natural products as a source of compounds with health benefits.